Planning seismic inner areas in Central Italy: Applications for the infrastructural project, lifeline and resilient public space in the shrinking territory - Marinelli, Giovanni; Domenella, Luca; Galasso, Marco; Rotondo, Francesco (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Natural calamities that repeatedly hit the Country, ranging from earthquake to climate change induced events – like landslides and floods – resulted in huge damages, worsened by the infrastructural degrade and by the abandonment of some territories, especially in the inner areas of the Country. There is therefore a pressing need to improve the infrastructural resiliency, focusing on extraordinary manutention, on the technological development of the monitoring activities and of the supporting infrastructure, on the prevention, the civil protection and the public aid. Peripheral urban contexts of the Inner Areas are exposed to “isolation Risks” in case of catastrophic events, as witnessed after the 2016 seismic events, where secondary infrastructure network was heavily affected, bringing great problems for those living in the areas. The paper explores experimental methodologies to bring substantial modifications to the villages and minor urban areas structure (for the damaged buildings as for the infrastructural network) that the reconstruction makes possible, making of it a unique occasion to renew and reorganize the territory.